2019
DOI: 10.1108/ejmbe-08-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Human capital: the link between leadership and organizational learning

Abstract: Purpose There is some research showing that leadership behaviors could be important antecedents to learning, but knowledge is scarce on the impact of which leadership styles support exploitative and explorative learning. The purpose of this paper is to hypothesize that transformational leadership – more concerned with innovation – will encourage generalist human capital (HC), while transactional leadership – more focused on the efficiency of existing operations – will promote specialist HC. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 90 publications
2
40
0
2
Order By: Relevance
“…Es importante considerar, la posición de Pasamar et al, (2019), que analizan a los líderes transformacionales, al preguntarse si existe motivación como característica elemental para una percepción adecuada de un clima laboral armonioso, los entrevistados dijeron que sí por el trato que les da la empresa estando reconocidos por ello y, por eso, hacen mucho más esfuerzo para producir mejor y con calidad por ser los propietarios personas que ejercen su liderazgo para bien de todos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Es importante considerar, la posición de Pasamar et al, (2019), que analizan a los líderes transformacionales, al preguntarse si existe motivación como característica elemental para una percepción adecuada de un clima laboral armonioso, los entrevistados dijeron que sí por el trato que les da la empresa estando reconocidos por ello y, por eso, hacen mucho más esfuerzo para producir mejor y con calidad por ser los propietarios personas que ejercen su liderazgo para bien de todos.…”
Section: Resultsunclassified
“…Existen autores como Arzu, Kalemci-Tuzun & Ozkan-Canbolat (2018), que sostienen que para evitar alteraciones en el comportamiento de los colaboradores, es necesario que se establezcan algunos alcances de paternalismo y acercamiento con ellos para hacer que estos se integren y perciban un clima laboral adecuado; por lo indicado los líderes transformacionales tienen mejores posibilidades de lograr liderazgo en sus colaboradores en relación con los líderes transaccionales que buscan personas especializadas en sus campos, como lo sostienen Pasamar, Diaz-Fernandez & De la Rosa Navarro, (2019).…”
Section: Neuroética Y Clima Laboral: Algunas Reflexiones Teóricasunclassified
“…Knowledge, as a critical organizational resource, can be rooted in the contemporary management schools of thought including the resource‐based theory of the firm (e.g., Barney, ; Nason & Wiklund, ; Wernerfelt, ), the knowledge‐based theory of the firm (Mouzas & Ford, ; Simao & Franco, ; Woiceshyn & Falkenberg, ), and the dynamic capability of the firm (e.g., Bowman & Ambrosini, ; Gutierrez‐Gutierrez, Barrales‐Molina, & Kaynak, ; Han & Li, ). The essence of these schools of thought asserts that a firm's ability to develop, use, and benefit from its knowledge and intellect through learning is the only source of sustainable competitive advantages (Pasamar, Diaz‐Fernandez, & de la Rosa‐Navarro, ; Seleim & Khalil, ; Torres et al, ). The more recent relevant research has increasingly recognized the importance of knowledge, particularly tacit knowledge, as a resource and its relevance to competitiveness and has proven to play a significant role in achieving excellence and innovation in organizations, whether these are for‐profit or not‐for‐profit organizations (Barrena‐Martinez, López‐Fernández, & Romero‐Fernández, ; Benevene, Kong, Barbieri, Lucchesi, & Cortini, ; Darroch & McNaughton, ; Mouzas & Ford, ; Wang et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of a firm’s knowledge capital and transformation of key knowledge into organisational learning (OL) is the greatest challenge to compete in the market (Amy, 2008). Intensive globalisation requires organisations to adapt to the changing environment by enhancing individual and organisational learning (Pasamar et al, 2019). Vashdi et al (2019) observed that organisations are oriented towards developing employee learning ability through providing opportunities to develop new ideas and share knowledge.…”
Section: Introductionmentioning
confidence: 99%